Ultrasound assessment of tensile stress in carotid arteries of healthy human subjects with varying age - Luo, Xianghong; Du, Lianfang; Li, Zhaojun (BMC medical imaging, 2019)
Arterial remodeling is thought to reflect the adaptation of the vessel wall to mechanical and hemodynamic stimuli and contributes to the progression of cardiovascular and cerebrovascular diseases. Tensile stress (TS) is one of the mechanical properties of the artery wall. The purpose of this study was to investigate the tensile stress change (TS) of carotid artery with varying viscoelasticity in healthy subjects within two groups of different ages. Forty-five subjects were recruited and randomly assigned into the group at the age above 50 years and below 50 years. The carotid arteries were examined by ultrasonography, using the techniques of shear wave elastography (SWE), shear wave dispersion (SWD) and radiofrequency (RF) -based ultrasound. The following values, including elastic modulus (SWER) and viscous index (SWDR), as well as the peak and mean TS of the left and right carotid arteries (L-PTS, R-PTS, L-MTS and R-MTS) were measured. The correlations between SWER, SWDR and tensile stress were evaluated. The SWE and SWD of carotid arteries are lower in the subjects ≥50 years old than the subjects younger than 50 years (SWE , 10.29 ± 9.57 kPa VS 17.24 ± 14.07 kPa; SWD 11.99 ± 3.51 (m/s)/kHz VS 13.97 ± 3.71 (m/s)/kHz, P < 0.05). The R-PTS was lower in the group with younger age (P < 0.05). Pearson correlation analysis showed that SWE of carotid artery was positively correlated with the parameters of tensile stress, R-PTS, R-MTS, L-PTS and L-MTS(r = 0.218, r = 0.359, r = 0.209 and r = 0.369, respectively, P < 0.05). However, SWD of carotid arteries was not significantly associated with TS. Ultrasonic shear wave imaging could be used to quantitatively assess carotid viscoelasticity. The carotid TS was related to its elasticity while little related to its viscosity, suggesting that mechanical properties of the arterial wall might be better revealed. Date of our trial registration: 2018-06-11. Registered with the official website of China Clinical Trial Registration Center (ChiCTR1800016590).